DISCRETE MOTOR SKILL ACQUISITION: EFFECT OF NUMBER OF VISUAL DEMONSTRATIONS - Alessandro Teodoro Bruzi; Rodolfo Novellino Benda; Leandro Ribeiro Palhares; João Vítor Alves Pereira Fialho; Herbert Ugrinowitsch (Journal of Physical Education)
ABSTRACT This experiment investigated the effect of number of visual demonstrations on the acquisition of discrete motor skill. Seventy-four college students of both sex participated in this study. The participants observed a visual model twice or ten times. In the acquisition phase, the participants were asked to throw a dart with postero-anterior movement into a circle target until reach a learning criterion. In transfer tests no difference between groups was found in the analysis of score. However, ten demonstrations were more effective than twice as regards performance of the correct pattern of movement and the number of subjects who reached the performance criterion. The results indicate a similar effect of the both number of demonstrations in the performance and dart throwing learning and both conditions influence subject’s capacity to detect relevant information to perform the task.